Theorizing hit-and-run: A study of driver decision-making processes after a road traffic collision. (February 2019) - Hopkins, Matt; Chivers, Sally
Explanations for driver decisions to hit-and-run have largely been based around a rational choice perspective that suggests drivers consider the expected costs of reporting a collision against the benefits of leaving the scene. Although such an explanation appears plausible, previous research has largely focused upon identifying contributory or contextual factors through analysis of quantitative datasets rather than engaging with drivers in order to understand how they make the decision to 'run'. This article explores the application of the rational choice perspective to hit-and-run driving. First, it develops an analytical framework based upon the rational choice decision-making process put forward by Tay et al. in 2008. Second, through analysis of 52 interviews with offenders, it examines how drivers structure the decision to leave the scene. Third, a typology of drivers is developed that illustrates that hit-and-run is not always based upon rational decision making. Finally, the article concludes with some implications for further research and the prevention of hit-and-run collisions.